1999
DOI: 10.1016/s0895-7061(99)00133-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of angiotensin II receptor blockade in humans using a standardized angiotensin II receptor-binding assay

Abstract: An in vitro angiotensin II (AngII) receptor-binding assay was developed to monitor the degree of receptor blockade in standardized conditions. This in vitro method was validated by comparing its results with those obtained in vivo with the injection of exogenous AngII and the measurement of the AngII-induced changes in systolic blood pressure. For this purpose, 12 normotensive subjects were enrolled in a double-blind, four-way cross-over study comparing the AngII receptor blockade induced by a single oral dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…Previous studies with ACEI and angiotensin II receptor antagonists have shown that increasing the dose once daily has little effect on the peak inhibition but tends to prolong the duration of the inhibition. In accordance with this observation increasing the dose of Losartan to 200mg (2 times higher than maximal recommended dose) once daily and that of Telmisartan to 160mg once daily significantly improved the trough blockade 68,69,70 . Another study with a total of 23 hypertensive patients with type 2 diabetes and nephropathy was carried out with four treatment periods, each lasting 2 months.…”
supporting
confidence: 75%
“…Previous studies with ACEI and angiotensin II receptor antagonists have shown that increasing the dose once daily has little effect on the peak inhibition but tends to prolong the duration of the inhibition. In accordance with this observation increasing the dose of Losartan to 200mg (2 times higher than maximal recommended dose) once daily and that of Telmisartan to 160mg once daily significantly improved the trough blockade 68,69,70 . Another study with a total of 23 hypertensive patients with type 2 diabetes and nephropathy was carried out with four treatment periods, each lasting 2 months.…”
supporting
confidence: 75%
“…BP, plasma Ang II concentration, plasma active renin concentration measurements, and neutralization of BP response to challenges with exogenous Ang I or Ang II 11 coupled with an in vitro Ang II radioreceptor binding assay quantifying the displacement of Ang II by RAS blockers 12 can be used to assess the intensity and duration of a RAS blockade. Even in controlled conditions, it is difficult to demonstrate small changes in BP in sodium-depleted normotensive subjects, especially 24 hours after drug intake, as shown in this experiment and in a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Antagonism of AT1R by various ARBs has also been tested in vivo in humans, mostly healthy volunteers, and, similar to the above animal studies, this was largely done for ANGinduced blood pressure elevations. Following the original study with losartan (Christen et al, 1991), such studies have been performed with candesartan (Delacretaz et al, 1995;Ogihara et al, 1995;Belz et al, 1997Belz et al, , 2000Malerczyk et al, 1998;Fuchs et al, 2000;Gleiter et al, 2004), irbesartan (Belz et al, 1999Maillard et al, 1999;Mazzolai et al, 1999), losartan (Munafo et al, 1992;Belz et al, 1997Belz et al, , 1999Belz et al, , 2000Maillard et al, 1999;Mazzolai et al, 1999;Fuchs et al, 2000;Gleiter et al, 2004), telmisartan Stangier et al, 2001), and valsartan (Müller et al, 1994;Morgan et al, 1997;Belz et al, 1999Belz et al, , 2000Maillard et al, 1999;Mazzolai et al, 1999).…”
Section: Antagonism In Vivomentioning
confidence: 99%